Sulfonated bio-based polyamide diaphragm as well as preparation method and application thereof
By using sulfonated biomass polyamide material to prepare lithium battery separators, the problem of poor bonding strength between the existing separator ceramic layer and the base film is solved, mechanical strength and thermal stability are improved, and the biomass of the material makes it more environmentally friendly.
Patent Information
- Application Number
- CN202411694628.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-11
AI Technical Summary
The existing lithium battery separators have weak bonding force between the ceramic layer and the base film, which is prone to coating peeling, and the petroleum-based aramid used has poor solubility and is unfriendly in the environment.
Using sulfonated bio-based polyamide material, a sulfonate polyamide slurry is formed by mixing diamine monomer with organic solvent under an inert atmosphere, and then reacting with furandiformyl chloride and a sulfonating agent, a sulfonate polyamide slurry is formed, and the membrane is prepared through an extrusion mechanism, and stretching and heat treatment are carried out.
The mechanical strength and thermal stability of the diaphragm are improved, and the problems of coating peeling and poor bonding of the base film are avoided. At the same time, due to the use of bio-based materials, the diaphragm is more environmentally friendly.
Smart Images

Figure BDA0005151817040000081 
Figure BDA0005151817040000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a sulfonated bio-based polyamide diaphragm and a preparation method and application thereof. Background Art
[0002] With the development of new energy vehicles, the performance requirements for lithium-ion batteries are getting higher and higher. In lithium batteries, the performance of the diaphragm is an important component of lithium batteries, and its performance is directly related to the performance of lithium batteries. Therefore, more and more research is being conducted on lithium battery diaphragms, with the aim of improving the various properties of the diaphragms, ensuring the safety of lithium batteries, and making the diaphragms play an increasingly important role in lithium batteries.
[0003] In the existing diaphragms, the slurry is usually coated on the base film, which mainly includes PP base film and PE base film. The diaphragm prepared by coating is prepared by coating one or more ceramic layers or other functional layers on the surface of the base film through a coating process based on the traditional lithium-ion battery diaphragm. The advantage of this process is that different coating materials can be selected as needed to improve certain specific properties of the diaphragm, such as improving thermal stability, mechanical strength or wettability. However, the diaphragm prepared by coating may have the problem of weak bonding between the ceramic layer and the base film, and the coating is prone to fall off. In addition, the existing slurry mainly includes ceramic and petroleum-based aramid. Petroleum-based aramid has poor solubility and strict requirements on molecular size. At the same time, the source of raw materials is unsustainable, and aramid itself is non-degradable. The diaphragm formed after coating does not meet the vision of long-term development.
[0004] Therefore, the existing diaphragms need to be improved. Summary of the invention
[0005] The purpose of the present invention is to provide a sulfonated bio-based polyamide diaphragm and a preparation method and application thereof, so as to solve the problems of coating shedding or poor bonding with the base membrane, and poor mechanical and thermal stability of the diaphragm.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a sulfonated bio-based polyamide diaphragm comprises the following steps:
[0008] (1) mixing a diamine monomer with an organic solvent under an inert atmosphere to obtain a diamine solution;
[0009] (2) mixing the diamine solution with furan dicarboxylic acid chloride at a temperature of 10 to 35° C. to obtain a furan-based polyamide solution;
[0010] (3) mixing the furan-based polyamide solution, the sulfonating agent and a cyclic sulfone solvent or a dialkyl sulfone solvent to obtain a sulfonated furan-based polyamide;
[0011] (4) neutralizing the sulfonated furan-based polyamide with an alkali to adjust the pH to 6 to 8, and then mixing with a plasticizer to obtain a sulfonic acid polyamide slurry;
[0012] (5) The sulfonic acid polyamide slurry is melted and extruded through an extruder, and then cooled and crystallized to obtain a casting sheet, which is then stretched and heat-treated to obtain a sulfonated bio-based polyamide diaphragm.
[0013] Furthermore, in step (1), the mass ratio of the diamine monomer to the organic solvent is 1:(4-10).
[0014] Further, in step (1), the diamine monomer is at least one of p-phenylenediamine, m-phenylenediamine, m-phenylenediamine, 4,4′-diaminodiphenyl ether and 1,2-ethylenediamine;
[0015] In step (1), the organic solvent is at least one of N,N-dimethylacetamide, N-methylpyrrolidone, acetone and 1,5-dimethyl-2-pyrrolidone.
[0016] Furthermore, in step (3), the cyclic sulfone solvent is cyclopentane sulfone, and the dialkyl sulfone solvent is at least one of dimethyl sulfone and dibutyl sulfone.
[0017] Furthermore, the molar ratio of furandicarboxylic acid chloride and diamine monomer is (1-1.2):1;
[0018] The mass ratio of the furan-based polyamide solution to the sulfonating agent is 1:(0.5-3);
[0019] The mass ratio of the sulfonating agent to the cyclic sulfone solvent or the dialkyl sulfone solvent is (0.1-0.6):1.
[0020] Furthermore, in step (3), the temperature of the mixed reaction is 30 to 150° C., and the time is 1 to 12 hours.
[0021] Further, in step (4), the plasticizer is at least one of diphenyl ether, xylene, toluene, paraffin oil and mineral oil;
[0022] The plasticizer accounts for 20% to 60% of the mass of the sulfonated furan-based polyamide.
[0023] Further, the alkali includes at least one of lithium carbonate, lithium hydroxide, sodium carbonate, sodium bicarbonate, sodium hydroxide, calcium hydroxide, potassium hydroxide and potassium carbonate. It should be noted that the alkali has alkalinity and is not limited to the types listed above. Specifically, lithium salts such as lithium carbonate and lithium hydroxide are preferred, because such lithium salts are not only alkaline and can play a neutralizing role, but also will not affect the transmission of lithium ions, thereby improving the lithium ion transmission performance of the diaphragm.
[0024] Furthermore, in step (5), the extrusion temperature is 160-250° C., the extrusion speed is 60-200 r / min, and the extrusion amount is 150-400 kg / h;
[0025] The cooling crystallization temperature is 10 to 30°C;
[0026] The stretching process comprises: firstly stretching the cast sheet longitudinally by 4 to 9 times at 90 to 150° C., and then stretching it transversely by 8 to 14 times;
[0027] The temperature of the heat treatment is 100°C to 150°C.
[0028] In a second aspect, the present invention provides a sulfonated bio-based polyamide membrane prepared by the above-mentioned preparation method.
[0029] In a third aspect, the present invention proposes an application of a sulfonated bio-based polyamide separator in a lithium battery.
[0030] Beneficial effects of the present invention:
[0031] In the present invention, a furan-based polyamide solution is first prepared, and then the obtained furan-based polyamide solution is mixed with a sulfonating agent and a cyclic sulfone solvent. The sulfonated polyamide solution has almost no effect on the sulfonation reaction because the cyclic sulfone solvent contains a sulfonyl group (-SO2-). The polyamide solution and the sulfonating agent are subjected to a sulfonation reaction in a cyclic sulfone solvent containing a sulfonyl group. The sulfonic acid group is grafted on the furan ring to avoid the molecular weight of the obtained polyamide being reduced by adding a sulfonating agent during the polymerization reaction. The sulfonated polyamide has a sulfonic acid group, which increases its affinity for water. The presence of the furan ring can increase the mechanical properties of the polymer. Then, the sulfonic acid polyamide is neutralized with an alkali to adjust the pH, and then mixed with a plasticizer to obtain a sulfonic acid polyamide slurry. Then, the sulfonic acid polyamide slurry is melted by an extruder to form a film, which is then stretched and heat-treated to obtain a sulfonated bio-based polyamide diaphragm. The furan-based polyamide itself is a polymer and has a furan ring, so that the diaphragm prepared by the wet method has high mechanical strength and high thermal stability.
[0032] The sulfonated bio-based polyamide diaphragm prepared by the present invention has high mechanical strength, strong hydrophilicity and is environmentally friendly. Since the diaphragm is prepared by integral molding, the problem of coating shedding or poor bonding with the base membrane that occurs in coated diaphragms will not occur, so the mechanical strength and thermal stability of the diaphragm are stronger.
[0033] In the present invention, furan-based polyamide is first generated, and then sulfonation reaction is carried out, and the sulfonation reaction is carried out in a cyclic sulfone solvent with a sulfonyl group, so as to avoid a decrease in the molecular weight of the obtained sulfonated bio-based polyamide, thereby facilitating the subsequent improvement of the mechanical strength of the diaphragm.
[0034] In the present invention, the polyamide uses a polyamide with a furan ring. The raw materials for synthesizing the furan-based polyamide can be derived from biomass, which is easily available, degradable, and environmentally friendly. In addition, the furan ring improves the strength and heat resistance of the polyamide, thereby improving the mechanical strength and heat resistance of the diaphragm.
[0035] In the present technical solution, a wet process is adopted to prepare the diaphragm, so as to avoid coating the prepared slurry on the base film, thereby eliminating the problem of weak bonding between the slurry and the base film, thereby further improving the mechanical strength and thermal stability of the diaphragm. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] Preparation of furan-based polyamide solution:
[0039] (1) Under a nitrogen atmosphere, 15 g of p-phenylenediamine and 100 g of N,N-dimethylacetamide were mixed to obtain a p-phenylenediamine solution;
[0040] (2) The obtained p-phenylenediamine solution was mixed with 27 g of furan dicarboxylic acid chloride at 15° C. to obtain a furan-based polyamide solution.
[0041] Preparation of sulfonic furan polyamide slurry:
[0042] (1) 10 g of furan-based polyamide solution and 100 g of cyclopentane sulfone were mixed and heated to 60° C., dissolved for half an hour, and then 24 g of chlorosulfonic acid was added dropwise, heated to 100° C., and stirred for reaction for 4 hours to obtain sulfonic furan-based polyamide; then the mixture was poured into water, filtered to obtain a solid, and the solid was repeatedly washed with deionized water to remove the solvent therein, and then dried at 100° C. to obtain a sulfonated furan-based polyamide (Mw: 196000).
[0043] (2) The sulfonated furan-based polyamide and lithium hydroxide are mixed, the pH is adjusted to 7, and then paraffin oil is added and mixed. The amount of paraffin oil added is 60% of the mass of the sulfonated furan-based polyamide.
[0044] Preparation of sulfonated bio-based polyamide diaphragm: then extruded by an extruder, the extrusion temperature is 210°C, the rotation speed is 120r / min, and the extrusion amount is 260kg / h. Then the extruded mixture is cooled and formed, and the cooling temperature is 10°C to obtain a cast sheet. The obtained cast sheet is first stretched 8 times longitudinally at 120°C, and then stretched 10 times transversely, and then the paraffin oil therein is extracted with dichloromethane. After the paraffin oil is separated, a preliminary formed diaphragm is obtained; finally, heat setting treatment is performed at 140°C, and then rolled up through a winding process to prepare a sulfonated bio-based polyamide diaphragm.
[0045] Preparation of lithium battery: button cell was prepared using the above separator.
[0046] Example 2
[0047] The difference between this embodiment and embodiment 1 is that the diamine monomer is different.
[0048] Preparation of furan-based polyamide solution: replace p-phenylenediamine with m-phenylenediamine, and the rest of the process is the same as Example 1.
[0049] Preparation of sulfonic furan polyamide slurry: The preparation process is the same as Example 1.
[0050] Preparation of sulfonated bio-based polyamide membrane: The preparation process is the same as that in Example 1, wherein the obtained sulfonated sulfonic acid polyamide (Mw is 206000) is obtained.
[0051] Example 3
[0052] The difference between this embodiment and embodiment 1 is that the cyclic sulfone solvent is different.
[0053] Preparation of furan-based polyamide solution: The preparation process is the same as Example 1.
[0054] Preparation of sulfonate furan polyamide slurry: 100 g of cyclopentane was replaced by 100 g of dimethyl sulfone, and the rest was the same as in Example 1. The obtained sulfonate furan polyamide (Mw: 187,000) was obtained.
[0055] Preparation of sulfonated bio-based polyamide membrane: The preparation process is the same as Example 1.
[0056] Preparation of lithium battery: The preparation process is the same as Example 1.
[0057] Example 4
[0058] The difference between this embodiment and embodiment 1 lies in adjusting the stretching parameters of the diaphragm preparation process.
[0059] Preparation of furan-based polyamide solution: The preparation process is the same as Example 1.
[0060] Preparation of sulfonic furan polyamide slurry: The preparation process is the same as Example 1.
[0061] Preparation of sulfonated bio-based polyamide diaphragm: Extrusion through an extruder, the extrusion temperature is 210°C, and the speed is 120r / min. Then the extruded mixture is cooled and formed, and the cooling temperature is 10°C to obtain a cast sheet. The resulting cast sheet is first stretched 7 times longitudinally at 120°C, and then stretched 12 times transversely, and then the paraffin oil therein is extracted with dichloromethane. After the paraffin oil is separated, a preliminary formed diaphragm is obtained; finally, heat setting treatment is performed at 140°C, and then rolled up through a winding process to prepare a sulfonated bio-based polyamide diaphragm.
[0062] Preparation of lithium battery: button cell was prepared using the above separator.
[0063] Example 5
[0064] The difference between this embodiment and embodiment 1 is that the type and amount of the plasticizer are adjusted.
[0065] Preparation of furan-based polyamide solution: The preparation process is the same as Example 1.
[0066] Preparation of sulfonated furan polyamide slurry: replacing paraffin oil with xylene, and the amount of xylene added is 25% of the mass of the sulfonated furan polyamide, and the rest of the process is the same as Example 1.
[0067] Preparation of sulfonated bio-based polyamide membrane: The preparation process is the same as Example 1.
[0068] Preparation of lithium battery: button cell was prepared using the above separator.
[0069] Example 6
[0070] The difference between this embodiment and embodiment 1 is that the type of sulfonating agent is adjusted.
[0071] Preparation of furan-based polyamide solution: The preparation process is the same as Example 1.
[0072] Preparation of sulfonic furan polyamide slurry: 24 g of chlorosulfonic acid was replaced by 24 g of concentrated sulfuric acid, and the rest was the same as in Example 1. The obtained sulfonic furan polyamide (Mw: 228,000) was obtained.
[0073] Preparation of sulfonated bio-based polyamide membrane: The preparation process is the same as Example 1.
[0074] Preparation of lithium battery: The preparation process is the same as Example 1.
[0075] Comparative Example 1
[0076] Compared with Example 1, the method of preparing the diaphragm in this comparative example is adjusted, and the coating method is adopted in this comparative example.
[0077] Preparation of furan-based polyamide solution: The preparation process is the same as Example 1.
[0078] Preparation of furan polyamide slurry: Preparation of sulfonate furan polyamide slurry: (1) Mix 10 g of furan polyamide solution and 100 g of cyclopentane sulfone, heat to 60°C, dissolve for half an hour, then add 24 g of chlorosulfonic acid dropwise, heat to 100°C, and stir to react for 4 hours to obtain sulfonate furan polyamide; then pour it into water, filter to obtain a solid, repeatedly wash the solid with deionized water to remove the solvent, and then dry the water at 100°C to obtain a sulfonated furan polyamide (Mw is 196000).
[0079] (2) The sulfonated furan-based polyamide and lithium hydroxide are mixed, the pH is adjusted to 7, and then paraffin oil is added and mixed. The amount of paraffin oil added is 60% of the mass of the sulfonated furan-based polyamide.
[0080] Preparation of lithium battery separator: coating the coating on a polyethylene base film with a coating thickness of 4 μm, and drying at 100° C. to obtain a separator.
[0081] Preparation of lithium battery: button cell was prepared using the above separator.
[0082] Comparative Example 2
[0083] Compared with Example 1, this comparative example replaces furan dicarboxylic acid chloride with terephthaloyl chloride.
[0084] Preparation of a polyamide solution: (1) Under a nitrogen atmosphere, 15 g of p-phenylenediamine and 100 g of N,N-dimethylacetamide were mixed to obtain a p-phenylenediamine solution;
[0085] (2) The obtained p-phenylenediamine solution was mixed with 27 g of terephthaloyl chloride at 15° C. to obtain a polyamide solution.
[0086] Preparation of sulfonic acid polyamide slurry: The preparation process is the same as Example 1.
[0087] Preparation of lithium battery separator: The preparation process is the same as Example 1.
[0088] Preparation of lithium battery: button cell was prepared using the above separator.
[0089] Comparative Example 3
[0090] In this comparative example, compared with Example 1, sulfolane was replaced by DMSO (dimethyl sulfoxide).
[0091] Preparation of furan-based polyamide solution: The preparation process is the same as Example 1.
[0092] Preparation of sulfonate furan polyamide slurry: replacing cyclopentane sulfone with DMSO to prepare sulfonate furan polyamide, whose Mw is 98000, and the rest of the process is the same as Example 1.
[0093] Preparation of lithium battery separator: The preparation process is the same as Example 1.
[0094] Preparation of lithium battery: The preparation process is the same as Example 1.
[0095] Comparative Example 4
[0096] Compared with Example 1, this comparative example replaces sulfolane with NMP (N-methylpyrrolidone).
[0097] Preparation of furan-based polyamide solution: The preparation process is the same as Example 1.
[0098] Preparation of sulfonate furan polyamide slurry: replacing cyclopentane sulfone with NMP to prepare sulfonate furan polyamide with a Mw of 94500. The rest of the process is the same as in Example 1.
[0099] Preparation of lithium battery separator: The preparation process is the same as Example 1.
[0100] Preparation of lithium battery: The preparation process is the same as Example 1.
[0101] The performance of the lithium battery separators obtained in Examples 1 to 6 and Comparative Examples 1 to 4 was tested, and the results are shown in Table 1:
[0102] Table 1
[0103]
[0104]
[0105] From the data of the diaphragms prepared in Examples 1 to 6, the diaphragms prepared by the present technical solution have high puncture strength, higher tensile strength, and lower thermal shrinkage, thereby improving the electrochemical performance of lithium batteries, improving battery safety, and extending battery life.
[0106] In Comparative Example 1, the prepared slurry was coated on a base film to prepare a diaphragm. From the test results, the mechanical properties of the diaphragm were significantly lower than those of the diaphragm prepared by the wet method. In Comparative Example 2, after the raw material furan dicarboxylic acid chloride was replaced, the generated polyamide no longer contained furan rings, and its strength decreased, which was manifested as a decrease in the mechanical properties of the prepared diaphragm. In Comparative Examples 3 and 4, after the sulfonated solvent was replaced with DMSO or NMP solvent, the molecular weight of the polyamide obtained after the sulfonation reaction decreased significantly, and thus the mechanical properties of the subsequent diaphragm were also significantly reduced.
[0107] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0108] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a sulfonated bio-based polyamide membrane, characterized in that: The steps include: (1) mixing a diamine monomer with an organic solvent under an inert atmosphere to obtain a diamine solution; (2) mixing the diamine solution with furan dicarboxylic acid chloride at a temperature of 10 to 35° C. to obtain a furan-based polyamide solution; (3) mixing the furan-based polyamide solution, the sulfonating agent and a cyclic sulfone solvent or a dialkyl sulfone solvent to obtain a sulfonated furan-based polyamide; (4) neutralizing the sulfonated furan-based polyamide with an alkali to adjust the pH to 6 to 8, and then mixing with a plasticizer to obtain a sulfonic acid polyamide slurry; (5) The sulfonic acid polyamide slurry is melted and extruded through an extruder, and then cooled and crystallized to obtain a casting sheet, which is then stretched and heat-treated to obtain a sulfonated bio-based polyamide diaphragm.
2. The method for preparing a sulfonated bio-based polyamide membrane according to claim 1, characterized in that: In step (1), the mass ratio of the diamine monomer to the organic solvent is 1:(4-10).
3. The method for preparing a sulfonated bio-based polyamide membrane according to claim 1, characterized in that: In step (1), the diamine monomer is at least one of p-phenylenediamine, m-phenylenediamine, m-phenylenediamine, 4,4′-diaminodiphenyl ether and 1,2-ethylenediamine; In step (1), the organic solvent is at least one of N,N-dimethylacetamide, N-methylpyrrolidone, acetone and 1,5-dimethyl-2-pyrrolidone.
4. The method for preparing a sulfonated bio-based polyamide membrane according to claim 1, characterized in that: In step (3), the cyclic sulfone solvent is cyclopentane sulfone, and the dialkyl sulfone solvent is at least one of dimethyl sulfone and dibutyl sulfone.
5. The method for preparing a sulfonated bio-based polyamide membrane according to claim 1, characterized in that: The molar ratio of furan dicarboxylic acid chloride and diamine monomer is (1-1.2):1; The mass ratio of the furan-based polyamide solution to the sulfonating agent is 1:(0.5-3); The mass ratio of the sulfonating agent to the cyclic sulfone solvent or the dialkyl sulfone solvent is (0.1-0.6):
1.
6. The method for preparing a sulfonated bio-based polyamide membrane according to claim 1, characterized in that: In step (3), the temperature of the mixed reaction is 30 to 150° C. and the time is 1 to 12 hours.
7. The method for preparing a sulfonated bio-based polyamide membrane according to claim 1, characterized in that: In step (4), the plasticizer is at least one of diphenyl ether, xylene, toluene, paraffin oil and mineral oil; The plasticizer is 20% to 60% of the mass of the sulfonated furan-based polyamide; The base includes at least one of lithium carbonate, lithium hydroxide, sodium carbonate, sodium bicarbonate, sodium hydroxide, calcium hydroxide, potassium hydroxide and potassium carbonate.
8. The method for preparing a sulfonated bio-based polyamide membrane according to claim 1, characterized in that: In step (5), the extrusion temperature is 160-250° C., the extrusion speed is 60-200 r / min, and the extrusion amount is 150-400 kg / h; The cooling crystallization temperature is 10 to 30°C; The stretching process comprises: firstly stretching the cast sheet longitudinally by 4 to 9 times at 90 to 150° C., and then stretching it transversely by 8 to 14 times; The temperature of the heat treatment is 100°C to 150°C.
9. A sulfonated bio-based polyamide membrane, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the sulfonated bio-based polyamide separator as claimed in claim 9 in a lithium battery.